Meningkatkan Kepedulian terhadap Kelestarian Lingkungan Hidup Melalui Pemilahan Sampah Mandiri - Yossita Wisman; Tutesa (Journal Pendidikan Ilmu Pengetahuan Sosial, 2020)
Almost all activities carried out by humans are not spared from producing used or residual activities or in other words is trash. Without realizing it, humans are producers waste, and if the management is not taken into account, then garbage will cause a lot of problems. So that human awareness of waste is very important for contribute to environmental sustainability and life man himself. As a source of waste, every household needs toplay a role in handling waste. If done together with the whole community, efforts to deal with waste can provide great benefits for environmental cleanliness and public health. making change is through understanding and knowledge. One important process for This article will discuss the importance of caring for environmental sustainability, the importance of management awareness household waste through sorting sampalh independently, as well donation of independent waste sorting for sustainability living environment.